Performance of 60-day Cowpea in the Fields of Uttarakhand Farmers: An Adoption Study - Surya Rathore (Indian Journal of Extension Education, 2017)
Farmer participatory trials of Pant Lobia 1, 2 &3 varieties of ’60-days cowpea’ were conducted on 236 farms in Uttarakhand and it was found through interviews and focused group discussions conducted on farmers’ fields that 60-day cowpea was short duration variety. Pant lobia 2 was more accepted as vegetable. Farmers had adopted simple practices like sowing time and method; harvesting and storage; selection and preparation of field and selection of variety. But important practices involving skills like weeding, disease and insect and pest management; seed treatment, fertilizer and nutrient management and irrigation were adopted by relatively less percentage of farmers. Majority of farmers had medium level of adoption of cowpea production technology and faced constraints like lack of knowledge about plant protection measures. Problem of land fragmentation was more severe in hills as compared to plains where prevalence of pests and diseases was more. It is implied that cooperative farming should be done in hills and specialized one day trainings can be organized by extension agencies on specific problems